Peningkatan Pengetahuan Masyarakat Jemaah Mesjid Ulil Amri Tentang Pencegahan Dan Penanganan Diare Di Tingkat Rumah Tangga - Rahmawati Rahmawati; Hasnah Hasnah; Effendy Rasiyanto (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2021)
Diarrhea can be prevented in various ways, including treating patients, providing health education about hygiene, and personal and environmental hygiene including water sources, trash cans, and disposal of feces. One of the efforts to prevent diarrheal disease is to provide counseling on diarrheal diseases. The selection of community service locations in Manggala Village, Manggala District, Makassar City, especially the Ulil Amri mosque congregation because the community, especially mothers do not have sufficient knowledge about proper hand washing, people who are not used to it. washing hands in every activity, and the community still lacks knowledge about diarrheal disease, its handling and prevention. Counseling in the context of community service is important because it can communicate information and materials about the dangers and possibilities of preventing diarrheal disease and protecting oneself, the community, and the environment from the spread of disease. Increasing public knowledge through counseling and demonstrations has shown very good results. The community was very enthusiastic about the material provided, the community was active in the question and answer session by seeing the many questions, opinions and experiences they issued that could be used to prevent and overcome diarrheal diseases and maintain environmental health.